Subjective and objective changes in visual quality after implantable collamer lens implantation for myopia - Nie, Li-li; Ma, Xiang; Pei, Ying (Frontiers in Medicine, 2025)
With the wide application of implantable collamer lens (ICL) surgery for myopia correction, the range of refractive correction has expanded (up to −18.00 D for myopia), and the safety, effectiveness, predictability and stability of ICLs have been well documented. However, achieving good visual quality after ICL implantation has also become very important. This article systematically reviews objective and subjective visual quality after ICL surgery. First, parameters used to assess objective visual quality after ICL surgery are introduced, including higher-order aberrations, the modulation transfer function (MTF) cutoff (cycles per degree [cpd]), the Strehl 2D ratio (SR), and the objective scatter index (OSI). Notably, various post-operative objective visual quality measurements have been improving over time. However, halos and glare caused by ICL implantation are notable postoperative complications. In further discussions, we also focus on factors that can affect visual quality, such as ICL position changes, pupil size, and the ICL optical zone. Furthermore, measures to improve postoperative visual quality, such as the selection of the surgical incision and mode, are provided. This review explores the potential mechanisms, emphasizes the importance of pre- and postoperative measures, and provides guidance for good postoperative visual quality. Additionally, this review aims to address the factors influencing visual quality and postoperative outcomes to optimize vision after ICL implantation.